2009
DOI: 10.1007/s00705-009-0323-y
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between SARS-CoV helicase and a multifunctional cellular protein (Ddx5) revealed by yeast and mammalian cell two-hybrid systems

Abstract: To reveal the putative cellular factors involved in SARS coronavirus replication, the helicase (Hel, nsp13) of SARS coronavirus was used to screen the cDNA library of rat pulmonary epithelial cells using the yeast two-hybrid system. Positively interacting proteins were further tested using a mammalian cell hybrid system and co-immunoprecipitation in the human A549 cell line, which has been shown to support SARS coronavirus replication. Out of the seven positive clones observed by yeast two-hybrid assay, only t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 36 publications
2
50
0
Order By: Relevance
“…Specific interactions of the DDX5 protein with the SARS-CoV helicase, nsp13, were confirmed in yeast and mammalian two-hybrid and coimmunoprecipitation experiments. Silencing of DDX5 expression led to reduced viral RNA replication and virus titers, supporting the biological significance of this interaction (Chen et al, 2009a). Similarly, in IBV and SARS-CoV, interactions between DDX1 and nsp14 were identified by yeast two-hybrid and coimmunoprecipitation assays (Xu et al, 2010) and validated by showing that knockdown of DDX1 expression affects coronavirus RNA replication and transcription.…”
Section: Possible Roles Of Cellular Proteins In Coronavirus Replicationmentioning
confidence: 70%
“…Specific interactions of the DDX5 protein with the SARS-CoV helicase, nsp13, were confirmed in yeast and mammalian two-hybrid and coimmunoprecipitation experiments. Silencing of DDX5 expression led to reduced viral RNA replication and virus titers, supporting the biological significance of this interaction (Chen et al, 2009a). Similarly, in IBV and SARS-CoV, interactions between DDX1 and nsp14 were identified by yeast two-hybrid and coimmunoprecipitation assays (Xu et al, 2010) and validated by showing that knockdown of DDX1 expression affects coronavirus RNA replication and transcription.…”
Section: Possible Roles Of Cellular Proteins In Coronavirus Replicationmentioning
confidence: 70%
“…One possible solution to overcome this problem is to target host cellular factors important for the viral life cycle. DDX5 plays important roles in many virus, such as SARS-CoV, influenza virus and HCV (Chen et al, 2009;Goh et al, 2004), and other cellular helicases such as DDX3, DDX1, DDX56 are also involved in many virus replication and the assembly of virions (Xu et al, 2011;Xu and Hobman, 2012). Two studies reported novel DDX3 inhibitors against HIV infection Radi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that DDX5 is involved in the replication of several viruses (Chen et al, 2009;Goh et al, 2004). To determine whether DDX5 is required for JEV replication, we first used shRNA-mediated gene silence method (DDX5i) to decrease the expression of endogenous DDX5 in BHK-21 cells.…”
Section: Endogenous Ddx5 Plays Important Role In Jev Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, cellular helicases may bind the RTC to assist coronavirus proteins in 3′-to-5′ unwinding. SARS-CoV nsp13 has been shown to interact specifically with the cellular RNA helicase DDX5, which is involved in coronavirus RNA synthesis (141). In addition, the cellular helicase DDX1 is recruited to RTCs, and the effects of DDX1 expression knockdown indicate that it might be an essential cofactor for coronavirus RNA replication and transcription (34, 142).…”
Section: Cellular and Viral Proteins Of The Coronavirus Replication-tmentioning
confidence: 99%